Relationship of eating habits to acute appendicitis in children: a literature review - Rizkiasa Nurafitha; Dian Adi Syahputra; Rima Novirianthy; Husnah; Munthadar (Journal of International Surgery and Clinical Medicine, 2022)
Introduction: Appendicitis is the inflammation of appendix vermiformis and is designated a national health priority issue by the Ministry of Health. Obstruction of the appendicitis lumen is the main etiology of acute appendicitis, and one of the risk factors is eating habits. This study aimed to determine how eating habits are at risk of causing appendicitis in children. Eating habits that were becoming the focus of this study are fiber intake, water consumption, and fast food. Methods: This research is a literature study with the scoping review method, compiled based on PRISMA-ScR. Results: The results obtained are four works of literature stating that low fiber intake and inadequate water consumption in children have a relationship with acute appendicitis, and one piece of literature states that there is no correlation. However, the consumption of fast food has no direct relationship to the occurrence of appendicitis. Conclusion: In this review, a low-fiber diet was significantly correlated with an increased incidence of appendicitis in children.